Trees for soil health and sustainable agriculture - R., Uthappa A.; Chavan, S. B.; Dhyani, S. K.; Handa, A. K.; Newaj, Ram (Indian Farming, 2016)
Tree based farming systems play an important role in maintaining the physico-biochemical properties of the soil thus sustaining the overall productivity. There is a huge task to check soil degradation throughout the country due to erroneous crop rotations being practiced in most parts of the country to achieve high productivity. To sustain the agriculture growth and productivity crop diversification by introducing tree based farming is most suitable choice. The tree component helps in maintaining the soil health and also for the improvement of degraded lands which can be later on taken up for regular cropping. The contribution of agroforestry in enhancing and maintaining the soil health and sustainability is a win-win situation for the small and marginal farmers.